(untitled) (Bangladesh Journal of Endosurgery, 2013)
Background: Ectopic pregnancy (EP) is a leading cause of pregnancy-related death in early pregnancy increasing in incidence worldwide. Ovarian ectopic pregnancy (OP) comprises 0.15% of all pregnancies and 1% to 3% of ectopic gestations. Case Report: A patient who was detected with OP was treated with laparoscopic surgery is described. The patient was admitted through emergency or outpatient department and managed by laparoscopy. The diagnosis of ovarian pregnancy was based on history, clinical symptoms, physical examination, a positive serum B-human chorionic gonadotropin (B-HCG), and transvaginal ultrasonography. Patient was informed pre-operatively about the surgical procedures. In the patient, ovarian wedge resection was performed to restore and preserve the ovarian tissue. There was no further therapeutic intervention in the follow-up course. Postoperative recovery period was normal. Conclusion: Primary OP may occasionally occur in patients with a suspected EP. Signs and symptoms suggestive of extrauterine pregnancy, TVS, and serum ?-hCG dynamics can be a useful adjunct to allow the preoperative diagnosis of OP prior to the use of the diagnostic gold standard, diagnostic laparoscopy. Preservation of ovarian tissue should be the therapeutic goal to maintain ovarian reserve and preserve fertility in young women with OP. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0016 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 39-42